2020
DOI: 10.1093/tas/txaa156
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the acute phase immune response to a lipopolysaccharide (LPS) challenge are mitigated by supplementation with a Saccharomyces cerevisiae fermentation product in weaned beef calves1,2

Abstract: This study was conducted to determine if feeding a Saccharomyces cerevisiae fermentation product (SCFP) to calves would alter the acute phase response to a lipopolysaccharide (LPS) challenge. Crossbred steer calves (n = 32; 274 ± 1.9 kg BW) were randomly allotted to 2 treatment diets for 21 d: 1) Control, fed RAMP (Cargill, Dalhart, TX), and 2) SCFP, fed the Control ration supplemented with NaturSafe at 12 g·hd-1·d-1 mixed into the TMR (NaturSafe®, Diamond V, Cedar Rapids, IA). On d 22, steers were fitted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
18
1
Order By: Relevance
“…In response to a vaccine challenge, steers had a significant decrease in circulating neutrophils and lymphocytes, but this response was prevented in steers supplemented with a hydrolyzed yeast [ 47 ]. In contrast, beef steers supplemented with a Saccharomyces cerevisiae fermentation product (SCFP) prior to challenge with LPS were found to have greater concentrations of platelets and WBC populations, yet had reduced pro-inflammatory cytokine concentrations following the immune challenge [ 48 ]. The authors suggested that the greater WBC populations prior to the LPS challenge served to prime the immune system, preparing it for the challenge, and ultimately resulted in the decreased cytokine concentrations observed post-challenge.…”
Section: Immunity and Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to a vaccine challenge, steers had a significant decrease in circulating neutrophils and lymphocytes, but this response was prevented in steers supplemented with a hydrolyzed yeast [ 47 ]. In contrast, beef steers supplemented with a Saccharomyces cerevisiae fermentation product (SCFP) prior to challenge with LPS were found to have greater concentrations of platelets and WBC populations, yet had reduced pro-inflammatory cytokine concentrations following the immune challenge [ 48 ]. The authors suggested that the greater WBC populations prior to the LPS challenge served to prime the immune system, preparing it for the challenge, and ultimately resulted in the decreased cytokine concentrations observed post-challenge.…”
Section: Immunity and Metabolismmentioning
confidence: 99%
“…However, the authors suggested that peak haptoglobin values may not have been realized due to the sample collection interval. In contrast, beef steers supplemented with SCFP had greater serum concentrations of fibrinogen compared to non-supplemented steers following an LPS challenge [ 48 ]. Fomenky et al [ 51 ] also observed greater concentrations of serum amyloid A and C-reactive protein in Holstein steers supplemented with yeast during the weaning period.…”
Section: Immunity and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevations in cortisol were only present in serum samples collected via jugular venipuncture. No differences ( p = 0.90) in circulating TNF-α concentrations were observed, and concentrations were decreased in comparison to other immune challenge models such as lipopolysaccharide (LPS) [ 18 ]. However, a treatment effect was observed ( p = 0.02) in IL-6 concentrations ( Figure 7 ) such that ZinMet heifers had increased IL-6 concentrations compared to Zn200 but were similar to Zn100 from 6 to 24 h after the MH challenge.…”
Section: Resultsmentioning
confidence: 99%
“…As previously stated, nutraceuticals, such as LY and yeast-derived products, may also exert an indirect effect on the immune system through an alteration of the metabolism, improving the energy availability in the form of glucose [ 23 ]. In fact, the blood glucose levels were significantly higher after a LPS endotoxin challenge in beef steers fed with different yeast-derived products [ 33 , 34 ]. These two studies suggest that supplementation of yeast-derived products may improve energy availability during an immune challenge, which may be beneficial to allow a more rapid resolution.…”
Section: Discussionmentioning
confidence: 99%